Wall effects on the percolation of small grains in 2D ensembles - Vidales, Ana Maria (2004)
This work studies the dependence of percolation properties of bidimensional arrays of polydispersed disks on the distance separating the walls of the container holding them. Data for percolation probabilities using different wall separation is analyzed for two extreme values of polydispersity. Conclusions on the effect that the container width has on the behavior of those properties are presented and discussed.